Doping of silicon with phosphorus end-terminated polymers: source characterization and dopant diffusion in SiO2. Issue 11 (4th March 2021) - Perego, Michele; Seguini, Gabriele; Mascheroni, Edoardo; Arduca, Elisa; Gianotti, Valentina; Laus, Michele
Abstract : A polystyrene homopolymer with narrow molecular weight distribution ( M n = 2.3 ± 0.3 kg mol −1, Đ = 1.05 ± 0.01) and end-terminated with a phosphorus containing moiety has been used to form P δ-layers embedded into a SiO2 matrix. Abstract : A polystyrene homopolymer with narrow molecular weight distribution ( M n = 2.3 ± 0.3 kg mol −1, Đ = 1.05 ± 0.01) and end-terminated with a phosphorus containing moiety has been used to form P δ-layers embedded into a SiO2 matrix. The number of P atoms in the δ-layers has been stepwise increased from ∼5 × 10 13 to ∼1.6 × 10 14 atoms per cm 2 by repeated doping cycles. The P δ-layers have been tested as diffusion sources at temperatures ranging from 1000 to 1200 °C for different annealing times, up to 120 s. Variations of the diffusion coefficients with the annealing time have been observed and a clear dependence of diffusion coefficients on the P concentration has been highlighted. These results suggest the presence of two different P species diffusing through the SiO2 matrix; an initially fast diffusing P compound and a slow diffusing P atom incorporated into the oxide in a bound form. Collected data provide information about P diffusion in SiO2 that is fundamental to the development of predictive models for nanoscale doping processes based on the use of diffusion dopant sources generated by self-limiting reactions of dopant containing molecules onto deglazed or non-deglazed semiconductor substrates.